Reevaluation of methanol extract from Phoenix dactylifera var. sukkari fruit’s potential against acne-inducing bacteria - Reza Anindita; Intan Kurnia Putri; Maya Uzia Beandrade; Dede Dwi Nathalia; Melania Perwitasari (Universitas Islam Negeri Sumatera Utara, 2022)
One of the natural ingredients that is often developed as an antibacterial product is the date palm (Phoenix dactylifera). However, scientific evidence regarding the effectiveness of the antibacterial compounds contained in dates needs to be evaluated, considering that several previous studies have reported that dates are more dominant as antioxidants than as antibacterials. Therefore, it is necessary to reevaluate the antibacterial ability of the methanolic extract of the sukkari variety date palm against the three test bacteria that cause acne, namely P. acnes, S. epidermidis and S. aureus. This research aimed to determine the sensitivity of the three bacteria tested in response to the methanol extract of the sukkari dates. This research design is experimental. The samples tested were sukkari and the tested bacteria were P. acnes, S. epidermidis and S. aureus. Dates were extracted by maceration method and made in concentrations of 50%, 60%, 70%, 80% and 90%. Positive control was chloramphenicol antibiotic while negative control was sterile distilled water. All treatments including control (+) and (-) were given to the test bacteria using the Kirby Baeur method to see the diameter of the zone of inhibition of the test bacteria growth. The data was processed in tabular form and compared with the 2016 CLSI standard to see the sensitivity response of the test bacteria. Results of this research is the sukkari dates extract with concentrations of 50%, 60%, 70%, 80% and 90% was able to inhibit the growth of P. acnes, S. epidermidis and S. aureus bacteria with an interval of 7.0-10.0 mm in diameter of the zone of inhibition. All the tested bacteria showed a sensitivity response in the resistant category, so the sukkari dates fruit extract is not the main choice to be developed as a natural anti-acne product.